Transformational Leadership in Enhancing the Competitiveness of Islamic Educational Institutions Through Teacher Career Advancement - Azwar Arifin; Prim Masrokan Mutohar (The Faculty of Education and Teaching Training, 2026)
Strengthening the competitiveness of Islamic educational institutions requires effective human resource management, particularly through sustainable teacher career development. Despite the implementation of various professional advancement initiatives, teacher promotion continues to face persistent challenges, including limited scholarly productivity, insufficient professional mentoring, and inadequate institutional support. These constraints may hinder teachers' professional growth and reduce Islamic educational institutions' capacity to remain competitive in an increasingly dynamic educational environment. This study aims to examine the role of transformational leadership in enhancing the competitiveness of Islamic educational institutions by advancing teachers' careers. A qualitative approach employing a library research design was adopted. Data were collected through a literature review and analyzed using content analysis, including data reduction, categorization, interpretation, and synthesis. The findings reveal that transformational leadership plays a pivotal role in accelerating teacher career advancement by strengthening motivation, facilitating competency development, supporting scholarly publication, providing performance-based incentives, and ensuring continuous administrative assistance. Furthermore, teacher career advancement contributes to greater academic productivity, stronger institutional reputation, broader academic collaboration, and improved organizational competitiveness. The study also demonstrates that integrating transformational leadership with teacher career development provides a strategic mechanism for linking leadership practices to sustainable competitive advantage. These findings highlight transformational leadership as a critical driver of both teacher professional development and the long-term competitiveness of Islamic educational institutions.